South-West Africa - Eveleigh, William, 1882- (Salt Lake City, UT : Project Gutenberg, 2022)
"South-West Africa" by William Eveleigh is a historical account written in the early 20th century. The book aims to provide a comprehensive overview of South-West Africa, covering its geography, history, natural resources, and potential for development. It tackles the misconception that the region is merely a desert, instead highlighting its diverse landscapes and cultural richness. The opening of the book presents a foreword that establishes the author's intent to fill a gap in English literature regarding South-West Africa's modern context. Eveleigh describes the territory$1 (Bs geographic features, including its coastal areas, plateaus, and rivers, while also giving an insightful overview of the climate and rainfall patterns. He seeks to convey a clear understanding of the land's complexities and potential, thus urging readers to reconsider the area's value beyond its arid reputation. The foreword also acknowledges the contributions of various individuals who aided in the compilation of this account, framing the narrative as both a personal and scholarly endeavor. (This is an automatically generated summary.)s
The land -- Climate and rainfall -- The flora of the country -- The fauna of the country -- The early days -- The later historical development -- The German occupation -- The people of the country -- The development of the country -- The diamond fields -- The economic future of the country.
Release date is 2022-03-19
The Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Namibia